2021
DOI: 10.1016/j.lanepe.2020.100004
|View full text |Cite
|
Sign up to set email alerts
|

European first responder systems and differences in return of spontaneous circulation and survival after out-of-hospital cardiac arrest: A study of registry cohorts

Abstract: Background In Europe, survival-rates after out-of-hospital cardiac arrest (OHCA) vary widely between regions. Whether a system dispatching First Responders (FRs; main FR-types: firefighters, police officers, citizen-responders) is present or not may be associated with survival-rates. This study aimed to assess the association between having a dispatched FR-system and rates of return of spontaneous circulation (ROSC) and survival across Europe. Methods Results of an inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 30 publications
0
21
0
1
Order By: Relevance
“…For the professional FRs, the situation is different because they are often equipped with an AED and can bring the defibrillator to the OHCA scene when alerted, resulting in a reduction of the time to the first defibrillation, which is associated with an increased chance of survival [35]. The effectiveness and the capability of the FR system to increase survival is already well-documented [8]. In our survey, we found that only in 11 out of 19 countries were the professional FRs alerted by the EMS equipped with an AED, stressing the need to improve this aspect throughout Europe.…”
Section: Aed Mapping and First Responder Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the professional FRs, the situation is different because they are often equipped with an AED and can bring the defibrillator to the OHCA scene when alerted, resulting in a reduction of the time to the first defibrillation, which is associated with an increased chance of survival [35]. The effectiveness and the capability of the FR system to increase survival is already well-documented [8]. In our survey, we found that only in 11 out of 19 countries were the professional FRs alerted by the EMS equipped with an AED, stressing the need to improve this aspect throughout Europe.…”
Section: Aed Mapping and First Responder Systemsmentioning
confidence: 99%
“…Early defibrillation increases not only the rate of return of spontaneous circulation (ROSC) and survival but also a favorable neurological outcome at the hospital discharge, irrespective of it being a witnessed event, bystander CPR or an initial rhythm [3][4][5]. AED use by a bystander or first responders (FRs; i.e., police officers, firefighters, off-duty medical personnel and trained lay persons alerted when a patient experiences an OHCA nearby) before the arrival of emergency medical service (EMS) personnel is of a primary importance particularly when considering that the earlier the defibrillation, the higher the chance of survival [6][7][8]. This concept was proven in the early 2000s, when the public-access defibrillation (PAD) trial was carried out in the USA involving security officers after cardiac arrests in casinos [9] and has been continuously reinforced by numerous scientific publications subsequently released [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…SCA is a major public health problem, causing 20% of total mortality in industrialized societies (7,8). SCA most often occurs in the community (out-of-hospital cardiac arrest) where rescuers are most often too late to arrive, resulting in low survival rates, ranging from 4 to 27% across Europe (9). Moreover, those who survive may suffer significant and persistent disabilities due to long-lasting hypoperfusion of the heart and the brain (7,10).…”
Section: Introductionmentioning
confidence: 99%
“…FR are usually alerted by smartphone and arrive earlier on scene than the EMS, leading to an earlier start of CPR [6,[13][14][15]. Approximately half of all European countries have implemented-to some degree-FR schemes [16] and the number is growing fast. FR schemes are associated with increased survival [7,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%